MENJADIKAN CINTA SEBAGAI PRINSIP NORMATIF DALAM PENDIDIKAN AGAMA KATOLIK: ANALISIS FILOSOFIS DAN KATEKETIS ATAS FRATELLI TUTTI - Patricius Neonnub; Octovianus Kosat (Lembaga Penelitian STKIP Widya Yuwana, 2026)
The global ethical crisis, intensified by digital culture, has reduced love to a mere emotional expression, stripping it of its normative force in the public sphere. Pope Francis’ encyclical Fratelli Tutti (2020) offers a corrective by presenting love as the foundation of universal fraternity; however, its integration into Catholic religious education remains underexplored. This study aims to analyze love as a normative principle through the lens of Thomistic meta-ethics (ordo amoris) and examine its pedagogical implications for Catholic Religious Education in the digital era. Employing a philosophical-theological analysis and critical document study, this research synthesizes magisterial teaching, Aquinas’ moral teleology, and contextual catechetical methodologies. The primary contribution of this work lies in mapping a conceptual pathway from normative ethics to pedagogy by embedding ordo amoris into instructional strategies responsive to pluralism and algorithmic polarization. Findings affirm that a Catholic education grounded in normative love not only resists sentimental moralism but also functions as a transformative agent for social renewal, advancing the vision of universal fraternity advocated in Fratelli Tutti.